Sustainable Business Models in Tourism - Szromek, Adam R. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
We invite you to read the Special Issue on business models in tourism, in the context of considering the principles of sustainable development. It is a collection of 14 articles published in a Special Issue of Sustainability MDPI in 2019-2021. The dynamic changes taking place in the world economy, social life, and the natural environment force entrepreneurs to change their business models. This also happens in the tourism business. The SARS-COV2 virus pandemic has increased the need for change. It is necessary to offer managers modern management tools that cover the broadest possible scope of integration of the elements of the conducted business activities, at the same time adjusted to the specificity of the market and needs of the natural environment in which the enterprises managed by them operate. This book, formulated in the light of the presented needs, aims to use the concept of business models and sustainability business models in the context of a tourism enterprise adapted to the existing conditions of tourist and spa activities.